2020
DOI: 10.1139/gen-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways associated with duck (Anas platyrhynchos) embryonic skin development using weighted gene co-expression network analysis

Abstract: Skin and feather follicle morphogenesis are important processes for duck development, however, the mechanisms underlying morphogenesis at the embryonic stage remain unclear. To improve understanding of these processes, we used transcriptome and weighted gene co-expression network analyses to identify these critical genes and pathways involved in duck skin development. Five modules were found to be the most related to five key stages in skin development that span from embryonic day 8 (E8) to postnatal day 7 (D7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Frahmm et al [9] suggested that this abnormal increase in brain tissue in crested-cushion chickens might be related to their similarly large ventricles. Our group previously found that there are fat-body-like lipomas in the brains of crestedcushion ducks, with some cranium missing or incompletely closed in the head and a small part of fat body tissue and brain tissue spillage, which is consistent with the findings of Bartels et al [2,10,11].…”
Section: Introductionsupporting
confidence: 91%
“…Frahmm et al [9] suggested that this abnormal increase in brain tissue in crested-cushion chickens might be related to their similarly large ventricles. Our group previously found that there are fat-body-like lipomas in the brains of crestedcushion ducks, with some cranium missing or incompletely closed in the head and a small part of fat body tissue and brain tissue spillage, which is consistent with the findings of Bartels et al [2,10,11].…”
Section: Introductionsupporting
confidence: 91%
“…Moreover, Abe et al (2017) [ 56 ] reported that PTCH1 is expressed in the epithelial and dermal sections of the early hair follicle at the start of the organogenesis phase of mouse hair follicle development, though a rise in PTCH1 expression is seen in the follicular dermal mesenchyme. In addition, Yuan et al (2020) [ 57 ] showed that among critical module genes involved in skin and feather follicle development in duck embryos, PTCH2, PTCH1, and Shh were identified as hub genes, were significantly expressed at E15, and are enriched in the Hedgehog (HH) signaling pathway. These findings suggest that this gene is highly related to skin and feather follicle formation and is acting through the regulation of the Shh signaling pathway.…”
Section: Discussionmentioning
confidence: 99%